1988
DOI: 10.1902/jop.1988.59.9.604
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of the Effect of Initial Periodontal Therapy on Thickness of the Maxillary Sinus Mucosa

Abstract: The thickness of the radiographic image of the maxillary sinus mucosa on intraoral radiographs was evaluated in 13 patients with advanced periodontal disease, prior to and 12 months following initial periodontal therapy. Before treatment, a relationship was observed between the thickness of the sinus mucosa and the mean probing depths of the teeth in the involved sextant. As many as 79% of the available sextants showed swelling of the mucosa prior to periodontal therapy, compared to only 17% after treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 8 publications
5
38
0
4
Order By: Relevance
“…These findings were supported by histopathological observations that severe periodontitis of the maxillary molars was clearly related to a thickening of the mucous membrane in the maxillary sinus [17]. Several studies using conventional radiography (periapical X-ray, panorama) reported that periodontitis was related with the severity and prevalence of mucous abnormality in maxillary sinus [10-13]. Bomeli et al [18], who studied acute odontogenic inflammation of the maxillary sinus by CT, reported that oral maxillary sinus fistula and periodontitis were distinct causes of inflammation compared with that of caries or periapical abscess.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These findings were supported by histopathological observations that severe periodontitis of the maxillary molars was clearly related to a thickening of the mucous membrane in the maxillary sinus [17]. Several studies using conventional radiography (periapical X-ray, panorama) reported that periodontitis was related with the severity and prevalence of mucous abnormality in maxillary sinus [10-13]. Bomeli et al [18], who studied acute odontogenic inflammation of the maxillary sinus by CT, reported that oral maxillary sinus fistula and periodontitis were distinct causes of inflammation compared with that of caries or periapical abscess.…”
Section: Discussionmentioning
confidence: 76%
“…Many studies have been conducted on the relationship between periodontal disease and mucosal thickening in the sinus membrane [11-13]. However, these reports were usually made at a time when teeth were still present, and there have been no studies conducted on the changes in the mucous membrane after extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Sinus expansion following extraction can greatly decrease the amount of bone height available for implant placement 1. A periapical or periodontal infection of the upper premolars and molars may spread beyond the confines of the supporting dental tissue into the maxillary sinus, causing sinusitis 3,7,8. Endodontic therapy or extraction of these teeth can result in penetration,9 oroantral fistulae or root displacement into the sinus cavity 10.…”
Section: Introductionmentioning
confidence: 99%
“…O conhecimento da relação dos ápices radiculares com o SM é importante para o diagnóstico e, consequente prevenção de infecções na cavidade sinusal, originadas de lesões periapicais e periodontais (ENGSTROM et al, 1988;HAUMAN;CHANDLER;TONG, 2002).…”
Section: Resultsunclassified
“…As alterações fisiológicas da membrana sinusal podem estar relacionadas com infecções dentárias, como periodontite, granuloma periapical e com maior frequência, com a infecção das vias aéreas superiores (ENGSTROM et al, 1988).…”
Section: Resultsunclassified